Beyond the manual: using research and evidence in social work practice - Grady, Melissa D.; Keenan, Elizabeth King (Clinical Social Work Journal, 2014)
There is a growing divide in social work between those that believe social work interventions should be based on either art or science. We argue that these positions create a false dichotomy within the profession, possibly due to the language associated with clinical work and research. In this introduction article of the Special Issue: Beyond the Manual, we outline the debate within social work around the art and science split and then offer a new approach to framing the issue. We argue that social workers are regularly approaching their work with clients using art and science simultaneously and describe a new frame for the profession. In an effort to articulate and promote this new frame, this special issue was born. This introductory article concludes with a brief description of the topics and articles included in the issue to orient the reader to the content included within it.
11 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/115-623-556-720-515 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Clinical judgment; Common elements; Common factors; Evidence-based practice; empirically-supported interventions; Research; dept.swk